Evidence-based framework to use in situ phycocyanin readings for cyanobacterial risk assessment within drinking water treatment plants - Ma, Liya; Dorner, Sarah; Prévost, Michèle (Environmental Science: Water Research & Technology, 2024)
A framework is proposed using multi-stream phycocyanin probe readings to manage cyanobacterial risks at the source water and across the drinking water treatment processes. , In situ phycocyanin (PC) probes have been deployed as a cost-effective and efficient way to monitor cyanobacterial (CB) abundance in drinking water sources and to identify periods of potential risk at drinking water treatment plants (DWTPs). Monitoring CB removal efficacies in near real-time by sequentially using a single probe for multiple streams across the treatment plant provides a more useful assessment of CB risk breakthrough in treated water. Removal efficacies were measured in three DWTPs using integrated mass fluxes estimated from PC readings and grab sample total CB biovolume estimations in raw, clarified, filtered, and treated water. Selective CB species removal during the treatment processes was also evaluated. In addition, relationships between physio-chemical parameters (turbidity, pH, dissolved oxygen, conductivity, chlorophyll-a and temperature) and PC across the treatment processes were investigated. Finally, a framework to use in situ multi-stream PC monitoring, gathering data across the treatment chain, is proposed to manage risks of CB cells breakthrough in treated water. Estimates of 2 hour moving average PC metrics are proposed to provide short term alert in raw water and establish periods of treatment vulnerability or dysfunction, while daily mean PC values can be used to estimate total and process specific log removals to justify treatment adjustments. Benefits and limitations of the tested in situ probes for the application of alert levels are discussed, and key knowledge gaps for future research and guidance are identified.
Keywords: Dorner_Sarah

Assessing the vulnerability of urban drinking water intakes to water scarcity under global change: A bottom-up approach - Leveque, Baptiste; Irakiza Shyaka, Albert; Ndong, Mouhamed; Jalbert, Jonathan; Burnet, Jean-Baptiste; Kammoun, Raja; Dorner, Sarah; Bichai, Françoise (Environmental Challenges, 2024)
Keywords: Dorner_Sarah